KOMUNIKASI INTERPERSONAL ANTARA KIAI DAN SANTRI DALAM MENANAMKAN NILAI-NILAI AKHLAKUL KARIMAH DI PONDOK PESANTREN AL- MUSTAQIM BUGEL - Khoirul Muslimin; Khoirul Umam (An-Nida : Jurnal Komunikasi Islam, 2019)
Interpersonal communication is fairly effective in telling, giving opinions or changing a person's behavior, because communication is reciprocal and the response from the communicant can be known directly. The purpose of this study was to determine the interpersonal communication processes and strategies between kiai and santri in instilling moral moral values in the Al-Mustaqim Islamic Boarding School of Bugel's son. This type is qualitative research w ith a hermeneutic phenomenology approach. The subjects of this study were kiai, administrators and students of the Islamic Boarding School Al-Mustaqim, the son of Bugel whose samples were taken through a snowball sampling technique. While the object is the process and interpersonal communication strategy. Data collection techniques are carried out by observation, documentation, interviewing and then the data is analyzed by data analysis methods, data reduction , data coding and data analysis. The results of this study are interpersonal communication processes and strategies carried out between kiai and santri in instilling akhlakul karimah values in Al-Mustaqim Islamic Boarding School in Bugel Village, namely direct communication with two forms of processes, namely the process of interpersonal communication in the session pengajian (through sorogan recitation method in dyadic communication and bandongan in small group communication) and non-recitation interpersonal communication process in (1) Boarding School Management Consultation: (2) Development of santri: (3) Special consultation. And interpersonal communication strategies, namely: (1) Dangled Carrot Strategy: (2) Dependent Sword Strategy.